A framework to define the relationship between cyber security and cloud performance. Issue 2 (February 2019) - Bhardwaj, Akashdeep; Goundar, Sam
Abstract : Cloud computing has become one of the most critical components of businesses and corporate organisations worldwide. It is a technology that has applications and services running on distributed networks and pooled virtualised resources that small, medium and large organisations can utilise to host their applications, processes and portals online via datacentres to provide access over the Internet to end users, customers and employees. In today's dynamic business world, traditional IT systems cannot keep up with ever-changing market demands and complex environments. Cloud computing has become one of the most critical components of enterprises worldwide. In today's dynamic business world, traditional IT systems cannot keep up with ever-changing market demands and complex environments. Many organisations are seeking an all-purpose cloud deployment to achieve increased service quality, which translates into better security and higher performance. In such cases, it becomes critical to concentrate on metrics for security and performance. Akashdeep Bhardwaj and Sam Goundar propose a framework for examining those two crucial elements.